CD47 (don't eat me signal) expression levels and its relationship with clinicopathologic features in early‐stage prostate carcinoma. Issue 16 (28th August 2022) - Semiz, Hüseyin S.; Küçük, Ülkü; Kısa, Erdem; Keskinkılıç, Merve; Süyün, Dilara Ecem; Arayıcı, Mehmet Emin; Atağ, Elif; Karaoglu, Aziz
Abstract: Background: Prostate cancer is a cancer with poor host immune response and could be defined as a non‐T‐cell inflamed tumor. Therefore, immunotherapy treatments could not be included in the treatment of prostate cancer until recently. Inadequate antitumoral response is one of the main reasons why tumor cells multiply rapidly and cause lethal results. It was shown that CD47 molecule, which is secreted at high levels by leukemia cells, reduces macrophage‐mediated phagocytosis and thus facilitates escape from the antitumoral immune response. The aim of this study was to show don't eat me signaling in prostate carcinoma tissues and its relationship with macrophage polarization. Materials and Methods: A total of 263 patients with a diagnosis of prostatic adenocarcinoma after radical prostatectomy between 2015 and 2020 at our institute were included in the study. CD47, CD68, and CD163 expression levels were examined immunohistochemically (IHC) in these tissues. The relationship of these expression levels with unfavorable prognostic factors and survival for prostate carcinoma was investigated. Results: In this study, all the operated prostate carcinoma cases had CD47 expression in tumor tissue, but only 52.5% had a high level of expression. Of 263 prostate cancer tissues, 135 (51.3%) showed high expression of CD68 protein and 189 (71.9%) showed high expression of CD163 protein. There was a statistically strong relationship between CD47, CD68, and CD163. Conclusions: The CD47 molecule is basically a molecule that inhibits macrophage activation. CD68 is mostly used for macrophage classification, while CD163 is used for tumor‐associated macrophage classification. Unlike others, we IHC examined CD47, CD68, and CD163 expressions in the surgical materials of patients who were operated for prostate carcinoma. In addition, we concluded that strong CD47 expression was closely associated with strong CD68 and CD163 expression in all tumor samples. However, a significant relationship between these expression levels and survival could not be demonstrated.